Fe-BASED NANOCRYSTALLINE ALLOY CORE AND METHOD FOR MANUFACTURING THE SAME

The Fe-based nanocrystalline alloy core with enhanced magnetic permeability at 100 kHz is achieved by using a ribbon with specific thickness, area ratio, and surface characteristics, addressing the need for improved high-frequency magnetic performance.

JP2025070836APending Publication Date: 2025-05-02PROTERIAL LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023181402
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

There is a need for an improvement in magnetic permeability at high frequency bands, particularly at 100 kHz, in Fe-based nanocrystalline alloy cores.

Method used

A Fe-based nanocrystalline alloy core is manufactured using a ribbon with a thickness of 11 μm to 14 μm and an area ratio of 73% or more, along with specific surface roughness and cross-sectional height characteristics, to enhance magnetic permeability.

Benefits of technology

The method achieves a higher magnetic permeability of 32,000 or more at 100 kHz, improving the magnetic properties and noise suppression capabilities of electrical and electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025070836000006
    Figure 2025070836000006
  • Figure 2025070836000007
    Figure 2025070836000007
  • Figure 2025070836000008
    Figure 2025070836000008
Patent Text Reader

Abstract

To provide an Fe-based nanocrystalline alloy core with a higher magnetic permeability and a method for manufacturing the Fe-based nanocrystalline alloy core.SOLUTION: The present invention relates to a core around which an Fe-based nanocrystalline alloy ribbon is wound. The Fe-based nanocrystalline alloy ribbon has a thickness of at least 11 μm and less than 14 μm. The occupation rate measured in accordance with IEC60404-8-11:2018 is at least 73%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an Fe-based nanocrystalline alloy core and a method for producing the Fe-based nanocrystalline alloy core. [Background technology]

[0002] As automobiles become more electric and semiconductors use higher frequencies, there is a demand for high impedance materials that cannot be realized with conventional product sizes in order to make the electronic devices they use more efficient and more compact. In recent years, Fe-based nanocrystalline alloys have been attracting attention.

[0003] For example, Patent Document 1 describes an Fe-based nanocrystalline alloy core that is wound with an Fe-based nanocrystalline alloy ribbon and has an impedance relative permeability μrz of 90,000 or more at a frequency of 10 kHz, 40,000 or more at a frequency of 100 kHz, and 8,500 or more at a frequency of 1 MHz. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2015 / 190528 Summary of the Invention [Problem to be solved by the invention]

[0005] There is a demand for improved magnetic permeability in the high frequency band, especially at 100 kHz.

[0006] An object of one embodiment of the present disclosure is to provide an Fe-based nanocrystalline alloy core having a higher magnetic permeability than conventional cores, and a method for manufacturing the Fe-based nanocrystalline alloy core. [Means for solving the problem]

[0007] <1> A core wound with an Fe-based nanocrystalline alloy ribbon, The Fe-based nanocrystalline alloy ribbon has a thickness of 11 μm or more and less than 14 μm, and an area fraction of 73% or more measured in accordance with IEC 60404-8-11:2018. <2> The Fe-based nanocrystalline alloy ribbon has one surface as a roll surface and the other surface as a free surface; The maximum peak height Rp of the roll surface is 1.2 μm or more, and the maximum valley depth Rv is 3.7 μm or less. <1> The Fe-based nanocrystalline alloy core according to claim 1. <3> The Fe-based nanocrystalline alloy ribbon has an arithmetic average roughness Ra of the roll surface of 0.6 μm or less. <2> The Fe-based nanocrystalline alloy core according to claim 1. <4> The Fe-based nanocrystalline alloy ribbon has a maximum cross-sectional height (Rt) of the roll surface of 4 μm to 7 μm. <2> or <3> The Fe-based nanocrystalline alloy core according to claim 1. <5> Winding the Fe-based amorphous alloy ribbon to prepare a core precursor; heating the core precursor; The Fe-based amorphous alloy ribbon has a thickness of 11 μm or more and less than 14 μm, and a space factor of 73% or more as measured in accordance with IEC60404-8-11:2018. <6> The Fe-based amorphous alloy ribbon has one surface as a roll surface and the other surface as a free surface, The maximum peak height Rp of the roll surface is 1.2 μm or more, and the maximum valley depth Rv is 3.7 μm or less. <5> A method for producing an Fe-based nanocrystalline alloy core according to claim 1. <7> The Fe-based amorphous alloy ribbon has an arithmetic average roughness Ra of the roll surface of 0.6 μm or less. <6> A method for producing an Fe-based nanocrystalline alloy core according to claim 1. <8> The Fe-based amorphous alloy ribbon has a maximum cross-sectional height Rt of the roll surface of 4 μm or more and 7 μm or less. <6> or <7> A method for producing an Fe-based nanocrystalline alloy core according to claim 1. <9> The method further comprises the step of preparing the Fe-based amorphous alloy ribbon, The step of producing the Fe-based amorphous alloy ribbon comprises: supplying a molten Fe-based alloy onto a surface of a chill roll; and injecting an atmospheric gas onto a surface of the chill roll to which the molten alloy is supplied. <5> ~ <8> 13. A method for producing an Fe-based nanocrystalline alloy core according to any one of claims 1 to 12. Effect of the Invention

[0008] According to the present disclosure, there is provided an Fe-based nanocrystalline alloy core having a higher magnetic permeability than conventional cores, and a method for manufacturing the Fe-based nanocrystalline alloy core. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a manufacturing apparatus for manufacturing an Fe-based amorphous alloy ribbon. [Diagram 2] FIG. 2 is a diagram showing an example of a circular Fe-based nanocrystalline alloy core. [Diagram 3] FIG. 3 is a diagram showing an example of an elliptical Fe-based nanocrystalline alloy core. [Figure 4] FIG. 4 is a diagram showing an example of an Fe-based nanocrystalline alloy core having a substantially rectangular shape. [Diagram 5] FIG. 5 is a diagram showing heating conditions in the production of an Fe-based nanocrystalline alloy core. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present disclosure will be described in detail below. In the present disclosure, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In the present disclosure, in the numerical ranges described stepwise, the upper limit or lower limit described in a certain numerical range may be replaced with the upper limit or lower limit of another numerical range described stepwise. In addition, in the numerical ranges described in this specification, the upper limit or lower limit described in a certain numerical range may be replaced with a value shown in the examples.

[0011] In the present disclosure, the term "process" refers not only to an independent process, but also to a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved.

[0012] In the present disclosure, the Fe-based nanocrystalline alloy ribbon refers to a ribbon (thin strip) made of an Fe-based nanocrystalline alloy. In addition, in the present disclosure, an Fe-based nanocrystalline alloy refers to a nanocrystalline alloy in which the element contained in the greatest amount (atomic %) among the metallic elements is Fe (iron).

[0013] In the present disclosure, the Fe-based amorphous alloy ribbon refers to a ribbon (thin strip) made of an Fe-based amorphous alloy. In the present disclosure, an Fe-based amorphous alloy refers to an amorphous alloy in which the metal element contained therein with the largest content (atomic %) is Fe (iron).

[0014] [Fe-based nanocrystalline alloy core] The Fe-based nanocrystalline alloy core of the present disclosure is a core wound with an Fe-based nanocrystalline alloy ribbon. The Fe-based nanocrystalline alloy ribbon has a thickness of 11 μm or more and less than 14 μm, and a space factor of 73% or more measured in accordance with IEC60404-8-11:2018.

[0015] The Fe-based nanocrystalline alloy core of the present disclosure has a space factor of the Fe-based nanocrystalline alloy ribbon of 73% or more, and therefore has a higher magnetic permeability than conventional cores. Patent Document 1 does not include any description focusing on the space factor of the Fe-based nanocrystalline alloy ribbon.

[0016] (Fe-based nanocrystalline alloy ribbon) The Fe-based nanocrystalline alloy ribbon has a thickness of 11 μm or more and less than 14 μm, and preferably 11 μm to 12 μm. Since the thickness of the Fe-based nanocrystalline alloy ribbon is 11 μm or more, the Fe-based nanocrystalline alloy ribbon is less likely to break during winding around the core, and can be wound continuously. The thickness of the Fe-based nanocrystalline alloy ribbon is less than 14 μm, so the current loss is small and the magnetic permeability of the Fe-based nanocrystalline alloy core is high.

[0017] The thickness of the Fe-based nanocrystalline alloy ribbon is measured by the following method. In accordance with IEC 60404-8-11:2018, it can be converted from the mass, length, width, and density of a 2000 mm long ribbon taken in the casting direction.

[0018] The Fe-based nanocrystalline alloy ribbon has a space factor of 73% or more, and preferably 75% or more. The upper limit of the space factor is not particularly limited, and is, for example, 77%. The space factor of the Fe-based nanocrystalline alloy ribbon is 73% or more, so the Fe-based nanocrystalline alloy core has high magnetic permeability.

[0019] The space factor of the Fe-based nanocrystalline alloy ribbon is measured by the following method. First, the mass, outer diameter, inner diameter, and height of the Fe-based nanocrystalline alloy core are measured. The volume of the Fe-based nanocrystalline alloy core is calculated from the outer diameter, inner diameter, and height. The space factor is calculated based on the following formula using the mass and volume of the Fe-based nanocrystalline alloy core and the density of the Fe-based nanocrystalline alloy ribbon. Space factor (%) = mass ÷ (volume x density)

[0020] The Fe-based nanocrystalline alloy ribbon preferably has a width dimension of 30 mm to 300 mm.

[0021] It is preferable that the Fe-based nanocrystalline alloy ribbon is formed such that one surface that is in contact with the cooling roll during production is the roll surface, and the other surface that is not in contact with the cooling roll is the free surface. The roll surface and the free surface can be visually distinguished by the gloss of the Fe-based nanocrystalline alloy ribbon surface. The roll surface is less glossy than the free surface because the unevenness of the cooling roll surface is transferred to the roll surface. Therefore, of the two surfaces of the Fe-based nanocrystalline alloy ribbon, the one that is glossier is the free surface, and the other that is not glossy is the roll surface.

[0022] The Fe-based nanocrystalline alloy ribbon has a roll surface having an arithmetic mean roughness Ra of preferably 0.6 μm or less, more preferably 0.1 μm to 0.6 μm. By making the arithmetic mean roughness Ra of the roll surface of the Fe-based nanocrystalline alloy ribbon 0.6 μm or less, it is possible to obtain an Fe-based nanocrystalline alloy ribbon with less unevenness on the roll surface. The arithmetic mean roughness Ra is measured in accordance with JIS B 0601:2001, with an evaluation length of 4.0 mm, a cutoff value of 0.8 mm, and a cutoff type of 2RC (phase compensation). The evaluation length is measured along the width direction (direction perpendicular to the casting direction) of the Fe-based nanocrystalline alloy ribbon at the center of the width direction. The free surface of the Fe-based nanocrystalline alloy ribbon tends to have a larger arithmetic mean roughness Ra than the rolled surface.

[0023] The Fe-based nanocrystalline alloy ribbon preferably has a maximum cross-sectional height Rt of 4 μm to 7 μm on the roll surface. By making the maximum cross-sectional height Rt of the Fe-based nanocrystalline alloy ribbon 4 μm or more, the insulation performance between the Fe-based nanocrystalline alloy ribbons is improved when wound around a core, and improved magnetic properties can be expected. By making the maximum cross-sectional height Rt of the Fe-based nanocrystalline alloy ribbon 7 μm or less on the roll surface, an Fe-based nanocrystalline alloy ribbon with less unevenness on the roll surface can be obtained, improving the space factor. The maximum cross-sectional height Rt is measured (evaluated) in accordance with JIS B 0601:2001, with an evaluation length of 4.0 mm, a cutoff value of 0.8 mm, and a cutoff type of 2RC (phase compensation). Here, the evaluation length is measured along the width direction (direction perpendicular to the casting direction) of the Fe-based nanocrystalline alloy ribbon at the center of the width direction.

[0024] The Fe-based nanocrystalline alloy ribbon preferably has a maximum peak height Rp of 1.2 μm or more on the roll surface, and more preferably 1.2 μm to 2.0 μm. By making the maximum peak height Rp of the Fe-based nanocrystalline alloy ribbon on the roll surface 1.2 μm or more, the insulation performance between the Fe-based nanocrystalline alloy ribbons is improved when wound around a core, and improved magnetic properties can be expected. The maximum peak height Rp is measured (evaluated) in accordance with JIS B 0601:2001, with an evaluation length of 4.0 mm, a cutoff value of 0.8 mm, and a cutoff type of 2RC (phase compensation). Here, the evaluation length is measured along the width direction (direction perpendicular to the casting direction) of the Fe-based nanocrystalline alloy ribbon at the center of the width direction.

[0025] The Fe-based nanocrystalline alloy ribbon preferably has a maximum valley depth Rv of 3.7 μm or less on the roll surface, and more preferably has a depth of 0.5 μm to 3.7 μm. By making the maximum valley depth Rv of the roll surface of the Fe-based nanocrystalline alloy ribbon 3.7 μm or less, it is possible to obtain an Fe-based nanocrystalline alloy ribbon with fewer concaves on the surface of the roll surface, and the space factor is improved. The maximum valley depth Rv is measured (evaluated) in accordance with JIS B 0601:2001, with an evaluation length of 4.0 mm, a cutoff value of 0.8 mm, and a cutoff type of 2RC (phase compensation). Here, the evaluation length is measured along the width direction (direction perpendicular to the casting direction) of the Fe-based nanocrystalline alloy ribbon at the center of the width direction.

[0026] The Fe-based nanocrystalline alloy ribbon preferably has a maximum height Rz of 3.0 μm to 5.0 μm on the roll surface. By making the maximum height Rz of the Fe-based nanocrystalline alloy ribbon roll surface 3.0 μm or more, the insulation performance between the Fe-based nanocrystalline alloy ribbons is improved when wound around a core, and improved magnetic properties can be expected. By making the maximum height Rz of the Fe-based nanocrystalline alloy ribbon roll surface 5.0 μm or less, an Fe-based nanocrystalline alloy ribbon with less unevenness on the roll surface can be obtained, improving the space factor. The maximum height Rz is measured (evaluated) in accordance with JIS B 0601:2001, with an evaluation length of 4.0 mm, a cutoff value of 0.8 mm, and a cutoff type of 2RC (phase compensation). Here, the evaluation length is measured along the width direction (direction perpendicular to the casting direction) of the Fe-based nanocrystalline alloy ribbon at the center of the width direction.

[0027] The Fe-based nanocrystalline alloy that constitutes the Fe-based nanocrystalline alloy ribbon preferably has Fe (iron) as the most abundant element (atomic percent) among the metal elements contained therein, and has an Fe-Si-B-Cu-Nb system composition.

[0028] The Fe-based nanocrystalline alloy contains at least Fe (iron), and preferably further contains Si (silicon) and B (boron), and more preferably contains copper (Cu) and niobium (Nb) in addition to Fe, Si, and B. The Fe-based nanocrystalline alloy may further contain C (carbon). Niobium (Nb) can be replaced with molybdenum (Mo) or vanadium (V), and a portion of iron (Fe) may be replaced with nickel (Ni) or cobalt (Co).

[0029] An example of an Fe-based nanocrystalline alloy is an Fe-based nanocrystalline alloy in which, when the total content of Fe, Si, B, Cu, Nb, C and unavoidable impurities is taken as 100 atomic %, the Fe content is 72 atomic % to 84 atomic %, the Si content is 2 atomic % to 20 atomic %, the B content is 5 atomic % to 14 atomic %, the Cu content is 0.2 atomic % to 2 atomic %, the Nb content is 0.1 atomic % to 5 atomic %, the C (carbon) content is 0.5 atomic % or less, and the remainder is impurities.

[0030] When the Fe content is 72 atomic % or more, the saturation magnetic flux density of the alloy ribbon is increased, and the increase in size or weight of the magnetic core manufactured using the alloy ribbon is suppressed.When the Fe content is 84 atomic % or less, the decrease in the Curie point and the decrease in the crystallization temperature of the alloy are suppressed, and the stability of the magnetic properties of the magnetic core is improved.

[0031] Furthermore, when the C (carbon) content is 0.5 atomic % or less, embrittlement of the alloy ribbon is further suppressed. The C (carbon) content is preferably 0.1 atomic % to 0.5 atomic %, and more preferably 0.15 atomic % to 0.35 atomic %. When the C (carbon) content is 0.1 atomic % or more, the productivity of the molten alloy and the alloy ribbon is excellent.

[0032] More preferably, when the total content of Fe, Si, B, Cu, Nb, C and unavoidable impurities is taken as 100 atomic %, the Si content is 12 atomic % to 18 atomic %, the B content is 5 atomic % to 10 atomic %, the Cu content is 0.8 atomic % to 1.2 atomic %, the Nb content is 2.0 atomic % to 4.0 atomic %, the C content is 0.1 atomic % to 0.5 atomic %, and the remainder is an Fe-based amorphous alloy consisting of Fe and unavoidable impurities. More preferably, when the total content of Fe, Si, B, Cu, Nb, C and unavoidable impurities is taken as 100 atomic %, the Si content is 14 atomic % to 16 atomic %, the B content is 6 atomic % to 9 atomic %, the Cu content is 0.9 atomic % to 1.1 atomic %, the Nb content is 2.5 atomic % to 3.5 atomic %, the C content is 0.15 atomic % to 0.35 atomic %, and the balance is an Fe-based amorphous alloy consisting of Fe and unavoidable impurities.

[0033] In each of the above-mentioned Fe-based amorphous alloys, the C (carbon) content is preferably 0.1 atomic % to 0.5 atomic % when the total content of Fe, Si, and B is taken as 100 atomic %.

[0034] (Magnetic permeability) The Fe-based nanocrystalline alloy core of the present disclosure preferably has a magnetic permeability at a frequency of 100 kHz of 32,000 or more, more preferably 36000 or more, and even more preferably 40000 or more. The upper limit of the magnetic permeability is, for example, 47000. The magnetic permeability here means the real part μr′ of the complex magnetic permeability. The magnetic permeability is calculated in the following manner. μr'=((OD+ID)×π×L) / (μ0×(OD-ID)×H×PF×N 2 )

[0035] OD: Outer diameter ID: Inner diameter μ0: Magnetic permeability in vacuum = 4π×10 -7 f: frequency PF: Space factor H: Height L: Inductance N: Number of turns when measuring L (1 turn)

[0036] FIG. 2 is a diagram showing an example of a circular Fe-based nanocrystalline alloy core. In FIG. 2, OD indicates the outer diameter, and ID indicates the inner diameter.

[0037] The Fe-based nanocrystalline alloy core of the present disclosure has high magnetic permeability at a frequency of 100 kHz, and can suppress noise when installed in electric / electronic devices.

[0038] The shape of the Fe-based nanocrystalline alloy core of the present disclosure is not particularly limited, and examples thereof include a circular shape, an elliptical shape, and a substantially rectangular shape.

[0039] FIG. 3 is a diagram showing an example of an elliptical Fe-based nanocrystalline alloy core.

[0040] When the Fe-based nanocrystalline alloy core has an elliptical shape, the magnetic permeability is calculated by the following method. First, the average magnetic path length and the effective cross-sectional area are calculated. Le: Average magnetic path length = 2(CA)+π(A+B) / 2 Ae: Effective cross-sectional area = {(AB) × H × PF} / 2 μr' = (Le × L) / (μ0 × Ae × N 2 )

[0041] A: The narrowest width of the elliptical circumference B: The narrowest width of the inner circumference of the ellipse C: The wider width of the oval circumference

[0042] FIG. 4 is a diagram showing an example of an Fe-based nanocrystalline alloy core having a substantially rectangular shape.

[0043] When the Fe-based nanocrystalline alloy core has a substantially rectangular shape, the magnetic permeability is calculated by the following method. First, the average magnetic path length and the effective cross-sectional area are calculated. Le: Average magnetic path length = (D-2R)+(E-2R)+π(R+R') Ae: Effective cross-sectional area = {(DF) × H × PF} / 2 μr' = (Le × L) / (μ0 × Ae × N 2 )

[0044] D: The wider width of the periphery of the approximately rectangular shape E: The narrowest width of the periphery of the approximately rectangular shape F: The wider width of the inner circumference of the approximately rectangular shape R: Curvature of the corners of the outer periphery of an approximately rectangular shape R': Curvature of the inner corner of the approximately rectangular shape

[0045] The Fe-based nanocrystalline alloy core of the present disclosure is suitable for pulse power magnetic parts used in common mode choke coils, inductors, various transformers, laser power supplies, accelerators, etc. These are made by winding a coil around the Fe-based nanocrystalline alloy core of the present disclosure.

[0046] [Method for producing Fe-based nanocrystalline alloy core] The method for producing an Fe-based nanocrystalline alloy core according to the present disclosure includes the steps of winding an Fe-based amorphous alloy ribbon to prepare a core precursor, and heating the core precursor.

[0047] (Core precursor preparation process) The core precursor preparation step is a step of winding an Fe-based amorphous alloy ribbon to prepare a core precursor. The Fe-based amorphous alloy ribbon has a thickness of 11 μm or more and less than 14 μm, and a space factor measured in accordance with IEC60404-8-11:2018 of 73% or more. The preferred embodiments of the thickness and space factor of the Fe-based amorphous alloy ribbon are the same as the preferred embodiments of the thickness and space factor of the Fe-based nanocrystalline alloy ribbon. The method for measuring the thickness and space factor of the Fe-based amorphous alloy ribbon is the same as the method for measuring the thickness and space factor of the Fe-based nanocrystalline alloy ribbon. The preferred composition of the Fe-based amorphous alloy ribbon is similar to the preferred composition of the Fe-based nanocrystalline alloy ribbon. The Fe-based amorphous alloy ribbon preferably has one surface as a roll surface and the other surface as a free surface. The preferred aspects of the properties of the roll surface of the Fe-based amorphous alloy ribbon are the same as the preferred aspects of the properties of the roll surface of the Fe-based nanocrystalline alloy ribbon.

[0048] (Core precursor heating process) The core precursor heating step is a step of heating the core precursor. In order to crystallize the Fe-based amorphous alloy into an Fe-based nanocrystalline alloy, it is preferable to heat the alloy at a temperature higher than the crystallization onset temperature of the Fe-based amorphous alloy. Specifically, the maximum temperature in the heating step is preferably at least 60° C. higher than the crystallization start temperature of the Fe-based amorphous alloy.

[0049] The crystallization onset temperature is determined by a differential scanning calorimetry. It is difficult to accurately measure the true crystallization onset temperature, so identification using a differential scanning calorimetry (DSC) is effective. The temperature at which an exothermic reaction due to the start of nanocrystallization is detected during heating is taken as the crystallization onset temperature. The crystallization onset temperature is measured at a heating rate of 10°C / min.

[0050] In the heating step, it is preferable to apply a magnetic field in the height direction of the core precursor.

[0051] The strength of the applied magnetic field is preferably 50 kA / m to 300 kA / m, and more preferably 60 kA / m to 280 kA / m.

[0052] The disclosed method for producing an Fe-based nanocrystalline alloy core may include a step of producing an Fe-based amorphous alloy ribbon.

[0053] (Fe-based amorphous alloy ribbon manufacturing process) The method for producing an Fe-based amorphous alloy ribbon will be described with reference to FIG.

[0054] Fig. 1 is a schematic cross-sectional view showing an example of a manufacturing apparatus for manufacturing an Fe-based amorphous alloy ribbon. The cross section of the alloy ribbon manufacturing apparatus is shown when it is cut along a plane perpendicular to the axial direction of the cooling roll 30 and the width direction of the alloy ribbon. Here, the alloy ribbon 22C is an example of an Fe-based amorphous alloy ribbon according to one embodiment of the present invention. In addition, the axial direction of the cooling roll 30 and the width direction of the alloy ribbon 22C are the same direction.

[0055] As shown in FIG. 1, an alloy ribbon manufacturing apparatus 100 includes a crucible 20 equipped with a molten metal nozzle 10 and a cooling roll 30 whose outer circumferential surface faces the tip of the molten metal nozzle 10 .

[0056] The crucible 20 has an internal space capable of accommodating the molten alloy 22A that is the raw material of the alloy ribbon 22C, and this internal space is connected to a molten metal flow path in the molten metal nozzle 10. This allows the molten alloy 22A accommodated in the crucible 20 to be discharged onto the chill roll 30 by the molten metal nozzle 10 (in FIG. 1, the discharge direction and flow direction of the molten alloy 22A are indicated by arrows Q). The crucible 20 and the molten metal nozzle 10 may be configured as an integral body or as separate bodies.

[0057] A high-frequency coil 40 serving as a heating means is disposed at least partially around the crucible 20. This makes it possible to heat the crucible 20 containing the master alloy of the alloy ribbon to generate the molten alloy 22A within the crucible 20, and to maintain the liquid state of the molten alloy 22A supplied to the crucible 20 from the outside.

[0058] The molten metal nozzle 10 also has an opening (discharge port) for discharging the molten alloy in the direction of the arrow Q. This opening is preferably a rectangular (slit-shaped) opening.

[0059] The distance (closest distance) between the tip of the molten metal nozzle 10 and the outer circumferential surface of the chill roll 30 is close enough that a puddle 22B (a pool of molten metal) is formed when the molten alloy 22A is discharged by the molten metal nozzle 10.

[0060] The chill roll 30 rotates about its axis in the direction of rotation P. A cooling medium such as water flows inside the chill roll 30, so that the coating of the molten alloy formed on the outer circumferential surface of the chill roll 30 can be cooled. By cooling the coating of the molten alloy, the alloy ribbon 22C(F ε-based amorphous alloy ribbon is produced.

[0061] Examples of materials for the cooling roll 30 include Cu and Cu alloys (Cu-Be alloy, Cu-Cr alloy, Cu-Zr alloy, Cu-Cr-Zr alloy, Cu-Ni alloy, Cu-Ni-Si alloy, Cu-Ni-Si-Cr alloy, Cu-Zn alloy, Cu-Sn alloy, Cu-Ti alloy, etc.), of which a Cu alloy is preferred due to its high thermal conductivity, and a Cu-Be alloy, a Cu-Cr-Zr alloy, a Cu-Ni alloy, a Cu-Ni-Si alloy, or a Cu-Ni-Si-Cr alloy is more preferred.

[0062] Although there is no particular limitation on the surface roughness of the outer peripheral surface of the chill roll 30, the arithmetic mean roughness (Ra) of the outer peripheral surface of the chill roll 30 is preferably 0.1 μm to 0.5 μm, and more preferably 0.1 μm to 0.3 μm. If the arithmetic mean roughness Ra of the outer peripheral surface of the chill roll 30 is 0.5 μm or less, the space factor is improved when manufacturing a wound magnetic core using the alloy ribbon. If the arithmetic mean roughness Ra of the outer peripheral surface of the chill roll 30 is 0.1 μm or more, adjustment of Ra is easier.

[0063] From the viewpoint of cooling capacity, the diameter of the chill roll 30 is preferably 200 mm to 1000 mm, more preferably 300 mm to 800 mm. The rotation speed of the chill roll 30 can be within the range usually set in the single roll method, but the peripheral speed is preferably 10 m / s to 40 m / s, more preferably 20 m / s to 30 m / s.

[0064] The alloy ribbon manufacturing apparatus 100 further includes a peeling gas nozzle 50 as a peeling means for peeling the Fe-based amorphous alloy ribbon from the outer peripheral surface of the chill roll, downstream of the molten metal nozzle 10 in the rotation direction of the chill roll 30 (hereinafter, simply referred to as the "downstream side"). In this example, the peeling gas nozzle 50 blows a peeling gas in the opposite direction to the rotation direction P of the chill roll 30 (the direction of the dashed arrow in FIG. 1) to peel the alloy ribbon 22C from the chill roll 30. As the peeling gas, for example, a high-pressure gas such as nitrogen gas or compressed air can be used.

[0065] The alloy ribbon manufacturing apparatus 100 further includes an abrasive brush roll 60 downstream of the peeling gas nozzle 50 as a polishing means for polishing the outer circumferential surface of the chill roll 30. The abrasive brush roll 60 includes a roll shaft member 61 and an abrasive brush 62 arranged around the roll shaft member 61. The abrasive brush 62 is made of a nonwoven fabric coated with a plurality of abrasive grains. The abrasive brush roll 60 rotates about its axis in the rotation direction R, thereby polishing the outer circumferential surface of the chill roll 30 with the nonwoven fabric of the abrasive brush 62.

[0066] The purpose of polishing by the polishing means (e.g., the polishing brush roll 60) is not necessarily limited to scraping the outer peripheral surface of the chill roll, but also includes removing residues remaining on the outer peripheral surface of the chill roll. The purpose of polishing is preferably at least one of the following first and second purposes.

[0067] The first purpose is to repair the deterioration of the smoothness of the outer peripheral surface of the chill roll. In detail, when the molten alloy and the outer peripheral surface of the chill roll first come into contact, a very small part of the outer peripheral surface of the chill roll (e.g., Cu alloy) dissolves in the molten alloy, and minute recesses (dropped parts) are formed on the outer peripheral surface of the chill roll, which may cause the deterioration of the smoothness of the outer peripheral surface of the chill roll. The deterioration of the smoothness of the outer peripheral surface of the chill roll may cause the deterioration of the smoothness of the roll surface of the alloy ribbon (the surface that was in contact with the outer peripheral surface of the chill roll; the same applies below). Even if the smoothness of the outer peripheral surface of the chill roll is deteriorated, the deterioration of the smoothness of the outer peripheral surface of the chill roll can be repaired by removing the parts that are convex relative to the minute recesses (dropped parts) by the above polishing almost evenly (i.e., the parts where dissolution is suppressed). As a result, the deterioration of the smoothness of the roll surface of the alloy ribbon caused by the deterioration of the smoothness of the outer peripheral surface of the chill roll can be suppressed.

[0068] The second purpose is to remove the residue (alloy) remaining on the outer peripheral surface of the cooling roll after the alloy ribbon is peeled off. The molten alloy discharged onto the outer peripheral surface of the cooling roll is rapidly cooled to form an alloy ribbon, which is then peeled off from the outer peripheral surface of the cooling roll. At this time, a part of the alloy, which is the material of the alloy ribbon, may remain as a residue without being peeled off from the outer peripheral surface of the cooling roll, and this residue may adhere to the outer peripheral surface of the cooling roll to form a convex portion. Since the casting of the alloy ribbon is performed continuously, the molten alloy is discharged again onto the outer peripheral surface of the cooling roll on which the convex portion due to the residue is formed. As a result, on the roll surface of the manufactured alloy ribbon, a concave portion may be formed at a position corresponding to the convex portion, and the smoothness of the roll surface of the alloy ribbon may be deteriorated. In addition, if the thermal conductivity of the residue (alloy) constituting the convex portion is lower than that of the outer peripheral surface of the cooling roll (e.g., Cu alloy), the rapid cooling characteristics by the cooling roll may be locally deteriorated at the convex portion, and the magnetic properties of the alloy ribbon may be deteriorated. Even if the above-mentioned residue remains on the outer peripheral surface of the cooling roll after the alloy ribbon is peeled off, the above-mentioned residue can be removed by the above-mentioned polishing. As a result, it is possible to suppress the deterioration of the smoothness of the roll surface of the alloy ribbon caused by the residue, and also to suppress the deterioration of the magnetic properties of the alloy ribbon caused by the residue.

[0069] The alloy ribbon manufacturing apparatus 100 further includes an atmospheric gas nozzle 70 for injecting (supplying) atmospheric gas onto the surface of the cooling roll onto which the molten alloy is supplied.

[0070] The atmospheric gas jetted from the atmospheric gas nozzle 70 is carbon dioxide gas or carbon monoxide gas in order to control the gas atmosphere in the vicinity of the roll surface at the nozzle tip.

[0071] The alloy ribbon manufacturing apparatus 100 may include other elements in addition to the elements described above (for example, a take-up roll for taking up the manufactured alloy ribbon 22C, etc.).

[0072] Next, an example of a method for manufacturing the alloy ribbon 22C using the alloy ribbon manufacturing apparatus 100 will be described. First, a molten alloy 22A serving as a raw material for the alloy ribbon 22C is prepared in the crucible 20. The temperature of the molten alloy 22A is appropriately set in consideration of the composition of the alloy, and is, for example, 1210°C to 1410°C, and preferably 1280°C to 1400°C.

[0073] Next, the molten alloy is discharged by the molten alloy nozzle 10 onto the outer peripheral surface of the cooling roll 30, which rotates in the rotation direction P, and a coating film is formed by the molten alloy while forming a puddle 22B. The formed coating film is cooled on the outer peripheral surface of the cooling roll 30, and an alloy ribbon 22C is formed on the outer peripheral surface. Next, the alloy ribbon 22C formed on the outer peripheral surface of the cooling roll 30 is peeled off from the outer peripheral surface of the cooling roll 30 by blowing a peeling gas from the peeling gas nozzle 50, and is wound up in a roll by a winding roll (not shown) and collected. Meanwhile, the outer peripheral surface of the cooling roll 30 after the alloy ribbon 22C is peeled off is polished by the polishing brush 62 of the polishing brush roll 60, which rotates in the rotation direction R. The molten alloy is again discharged onto the polished outer peripheral surface of the cooling roll 30. By repeating the above operations, the long alloy ribbon 22C is continuously manufactured (cast).

[0074] The method for manufacturing the Fe-based nanocrystalline alloy core of the present disclosure may include a step of impregnating the core into an epoxy resin diluted with an organic solvent after the heating step of the core precursor. After impregnation, it is preferably dried.

Example

[0075] Hereinafter, examples of the present disclosure will be presented, but the present disclosure is not limited to the following examples.

[0076] <Fabrication of Fe-based amorphous alloy ribbon> An alloy ribbon manufacturing apparatus similar to the alloy ribbon manufacturing apparatus 100 shown in FIG. 1 was prepared. As the cooling roll, a cooling roll having an outer peripheral surface made of a Cu-Be alloy, a diameter of 400 mm, and an arithmetic mean roughness Ra of the outer peripheral surface of 0.3 μm was used.

[0077] First, an alloy melt (hereinafter, also referred to as "Fe-Si-B-Cu-Nb-based alloy melt") composed of Fe, Si, B, Cu, Nb, C, and inevitable impurities was prepared in a crucible. Specifically, pure iron, ferrosilicon, and ferroboron were mixed and melted, and when the total content of Fe, Si, B, Cu, Nb, C, and inevitable impurities was 100 atomic%, the content of Si was 15 atomic%, the content of B was 7 atomic%, the content of Cu was 1 atomic%, the content of Nb was 3 atomic%, the content of C was 0.2 atomic%, and the balance was an alloy melt composed of Fe and inevitable impurities. The numerical values of atomic% are the amounts measured by ICP emission spectrometry by sampling a part of the alloy from the melt.

[0078] Next, this Fe-Si-B-Cu-Nb-based alloy melt was discharged from the opening of a melt nozzle having a rectangular (slit shape) opening with a long side length of 53 mm and a short side length of 0.3 mm onto the outer peripheral surface of a rotating cooling roll and rapidly solidified to produce (cast) 500 kg of an amorphous alloy ribbon with a ribbon width of 53 mm. The casting time was 60 minutes, and the alloy ribbon was continuously cast without breaking. The above casting was performed while polishing the outer peripheral surface of the cooling roll with a polishing brush (non-woven fabric) of a polishing brush roll.

[0079] The detailed conditions for casting are shown below. <Casting Conditions> Melt temperature of the alloy: 1350 °C to 1390 °C Peripheral speed of the cooling roll: 20 m / s to 30 m / s Discharge pressure of the alloy melt: Adjusted within the range of 5 kPa to 30 kPa Distance (gap) between the tip of the melt nozzle and the outer peripheral surface of the cooling roll: Adjusted within the range of 0.1 mm to 0.35 mm

[0080] <Fabrication of Fe-based nanocrystalline alloy core> The obtained Fe-based amorphous alloy ribbon was wound to fabricate a core precursor. The core precursor was heated with the profile shown in Fig. 5 to fabricate an Fe-based nanocrystalline alloy core. Specifically, it was held at 25 °C for 5 minutes, heated to 430 °C over 1 hour and 40 minutes, heated to 580 °C over 4 hours and 10 minutes, held at 580 °C for 10 minutes, and then cooled to 300 °C over 1 hour. Also, a magnetic field of 80 kA / m was applied in the range of 520 °C to 580 °C for 30 minutes.

[0081] In Example 1 and Comparative Example 1, the tension applied to the Fe-based amorphous alloy ribbon was adjusted to manufacture the stacking factor to the dimensions shown in Table 1.

[0082] The magnetic permeability of the fabricated Fe-based nanocrystalline alloy core was measured. The measurement results are shown in Table 1.

[0083]

Table 1

[0084] As shown in Table 1, in Example 1, for the core wound with the Fe-based nanocrystalline alloy ribbon, the Fe-based nanocrystalline alloy ribbon has a thickness of 11 μm or more and less than 14 μm, and the stacking factor measured in accordance with IEC60404-8-11:2018 is 73% or more. Therefore, it was found that the magnetic permeability is higher compared to Comparative Example 1. In Example 1, the magnetic permeability at a frequency of 100 kHz was 32,000 or more.

[0085] <Example 100> Next, the Fe-based amorphous alloy ribbon was used to fabricate a circular Fe-based nanocrystalline alloy core. The outer diameter, inner diameter, height, and weight are shown in Table 2. The magnetic permeability is the magnetic permeability at a frequency of 100 kHz.

[0086] [Table 2]

[0087] <Example 200> A circular Fe-based nanocrystalline alloy core was produced in the same manner as in Example 100, except that the impregnation step was carried out after the heating step of the core precursor. In the impregnation step, the heated core was impregnated with epoxy resin diluted with acetone. The outer diameter, inner diameter, height, and weight are shown in Table 3. The magnetic permeability is the magnetic permeability at a frequency of 100 kHz.

[0088] [Table 3]

[0089] <Example 300> After a circular Fe-based nanocrystalline alloy core was produced, it was molded to produce an elliptical Fe-based nanocrystalline alloy core as shown in FIG. The outer diameter, inner diameter, height, and weight before molding are shown in Table 4. The magnetic permeability is the magnetic permeability at a frequency of 100 kHz. In Table 4, A after molding means the narrower width of the outer periphery of the ellipse, and B after molding means the narrower width of the inner periphery of the ellipse.

[0090] [Table 4]

[0091] <Example 400> After a circular Fe-based nanocrystalline alloy core was produced, it was molded to produce a roughly rectangular Fe-based nanocrystalline alloy core as shown in FIG. The outer diameter, inner diameter, height, and weight before molding are shown in Table 5. The magnetic permeability is the magnetic permeability at a frequency of 100 kHz. In Table 5, D after molding means the wider width at the outer periphery of the approximately rectangular shape, E after molding means the narrower width at the outer periphery of the approximately rectangular shape, F after molding means the wider width at the inner periphery of the approximately rectangular shape, and G after molding means the narrower width at the inner periphery of the approximately rectangular shape.

[0092] [Table 5]

[0093] It was found from Examples 100 to 400 that Fe-based nanocrystalline alloy cores of various shapes having a magnetic permeability of 32,000 or more at 100 kHz could be obtained.

[0094] 10: Molten metal nozzle 20: Crucible 30: Cooling roll 40: High frequency coil 50: Stripping gas nozzle 60: Abrasive brush roll 70: Atmosphere gas nozzle 100: Alloy ribbon manufacturing equipment

Claims

1. A core wound with an Fe-based nanocrystalline alloy ribbon, The Fe-based nanocrystalline alloy ribbon has a thickness of 11 μm or more and less than 14 μm, and a space factor measured in accordance with IEC 60404-8-11:2018 of 73% or more.

2. The Fe-based nanocrystalline alloy ribbon has one surface as a roll surface and the other surface as a free surface; The Fe-based nanocrystalline alloy core according to claim 1, wherein the roll surface has a maximum peak height Rp of 1.2 μm or more and a maximum valley depth Rv of 3.7 μm or less.

3. The Fe-based nanocrystalline alloy core according to claim 2, wherein the Fe-based nanocrystalline alloy ribbon has an arithmetic mean roughness Ra of the roll surface of 0.6 μm or less.

4. The Fe-based nanocrystalline alloy core according to claim 2, wherein the Fe-based nanocrystalline alloy ribbon has a maximum cross-sectional height Rt of the roll surface of 4 μm or more and 7 μm or less.

5. A step of winding the Fe-based amorphous alloy ribbon to prepare a core precursor; heating the core precursor; The Fe-based amorphous alloy ribbon has a thickness of 11 μm or more and less than 14 μm, and a space factor measured in accordance with IEC 60404-8-11:2018 of 73% or more.

6. The Fe-based amorphous alloy ribbon has one surface as a roll surface and the other surface as a free surface, 6. The method for producing an Fe-based nanocrystalline alloy core according to claim 5, wherein the maximum peak height Rp of the roll surface is 1.2 μm or more and the maximum valley depth Rv is 3.7 μm or less.

7. The method for producing an Fe-based nanocrystalline alloy core according to claim 6, wherein the Fe-based amorphous alloy ribbon has an arithmetic mean roughness Ra of the roll surface of 0.6 μm or less.

8. The method for producing an Fe-based nanocrystalline alloy core according to claim 6, wherein the Fe-based amorphous alloy ribbon has a maximum cross-sectional height Rt of the roll surface of 4 μm to 7 μm.

9. The method further includes a step of preparing the Fe-based amorphous alloy ribbon, The step of producing the Fe-based amorphous alloy ribbon includes: supplying a molten Fe-based alloy onto a surface of a chill roll; The method for producing an Fe-based nanocrystalline alloy core according to any one of claims 5 to 8, further comprising the step of: injecting an atmospheric gas onto a surface of the chill roll to which the molten alloy is supplied.

Citation Information

Patent Citations

  • Fe-BASED NANOCRYSTALLINE ALLOY CORE AND METHOD FOR PRODUCING Fe-BASED NANOCRYSTALLINE ALLOY CORE

    WO2015190528A1